Influência do resfriamento da porcelana com e sem leucita na referência à fratura de sistemas com infraestrutura em zircônia - Meirelles, Potira Dalques (2015)
This study investigated the influence of porcelain cooling protocol with and without leucite in fracture resistance applied on zirconia. We tested the hypothesis that (1) the strength and reliability of the porcelain containing leucite are larger than the porcelain without leucite when applied on zirconia, and (2) slow cooling protocol results in greater strength than china cooling fast for both tested systems. Were prepared zirconia rods 120 (0.8 thick) were coated with 1 mm thick porcelain (total size 1.8 mm x 16 mm x 4mm). The bars were divided into four groups (n = 30) for application of different porcelains (with or without leucite), and cooling systems (fast or slow). The specimens were subjected to flexural strength testing in 3 points to the first sign of fracture, keeping the surface of the porcelain under traction. Data were analyzed by two-way ANOVA and Tukey test (95%). Analysis of Weibull and fracture were performed. The results showed that the resistance to fracture system containing leucite porcelain was similar to the system without leucite (p = 0.718). The cooling protocol used did not modify the flexural strength of the two groups (p = 0.761). The study hypotheses were rejected, since the presence of leucite and cooling did not significantly alter the fracture strength and reliability of the systems